Literature Study about Application Android Media on Biological Learning Process - Atmaja, Mahiaka Dwi; Raharjo, Raharjo (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
In the learning process needed a good strategy to achieve learning goals. One of them is the use of media so that the learning process runs well. The development of the times has brought the world of education more advanced because of the floating technology and information. Android is very popular and many people use it among the people. Many Android applications have been developed for education. In biology, there are a lot of material and need to help overcome material that is still abstract or unclear. A strategy is needed to overcome this, one of which is the use of Android application media. Literature study that have been published say that Android application media can significantly improve students' understanding. The media is also very effective because it has the characteristics of being flexible to use anytime and anywhere, interactive and communicative that can attract students, and make it easier to understand the material so that knowledge is more concrete and can support student learning outcomes. The effectiveness of android applications can be seen from the results of media user satisfaction and can be seen in research that has used applications. This can be seen from the completeness of the learning outcomes of students reaching â‰¥75%. Keywords: learning media, Android aplication, biology material, learning process, learning goals.